Unregistered Marriage in the Perspective of Islamic Legal Sociology - Hidayat, Irwan (GIC Proceeding, 2024)
Nikah siri, or unregistered marriage, is a common practice among Muslim communities, especially in Indonesia. This phenomenon has attracted attention from various disciplines, including Islamic legal sociology. In this research, we explore the sociological aspects of nikah siri within the context of Islamic law.By utilizing Islamic legal principles and sociological theories, this study aims to examine the prevalence, motivations, and consequences of nikah siri. Factors such as financial constraints, social pressures, and cultural norms contribute to the perpetuation of this practice. Additionally, nikah siri has significant ramifications for individuals, families, and society at large, impacting legal rights, social standing, and familial dynamics. Through a comprehensive analysis of nikah siri from a sociological standpoint grounded in Islamic legal principles, this research seeks to provide insights into the intricacies of this phenomenon. By understanding the socio-legal dynamics surrounding nikah siri, policymakers, legal practitioners, and community leaders can develop more effective strategies to address its challenges and mitigate its adverse effects on individuals and society